2020
DOI: 10.3748/wjg.v26.i30.4378
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the intestinal microbiota: An emerging therapeutic strategy for inflammatory bowel disease

Abstract: The rapid development of metagenomics, metabolomics, and metatranscriptomics provides novel insights into the intestinal microbiota factors linked to inflammatory bowel disease (IBD). Multiple microorganisms play a role in intestinal health; these include bacteria, fungi, and viruses that exist in a dynamic balance to maintain mucosal homeostasis. Perturbations in the intestinal microbiota disrupt mucosal homeostasis and are closely related to IBD in humans and colitis in mice. Therefore, preventing or correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 140 publications
(153 reference statements)
0
9
0
1
Order By: Relevance
“…8 In addition, previous studies have shown that additional intake of beneficial bacteria can compete with harmful bacteria for adhesion sites and restore the balance of the intestinal flora, which is a target for treating UC. 9 Probiotics are defined as live microorganisms that when given in adequate amounts, can provide health benefits to the host. 10 Probiotics usually promote health by regulating the endostasis of intestinal microorganisms, and Lactobacillus, Bifidobacterium and various probiotic complexes are widely used in UC alleviation studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In addition, previous studies have shown that additional intake of beneficial bacteria can compete with harmful bacteria for adhesion sites and restore the balance of the intestinal flora, which is a target for treating UC. 9 Probiotics are defined as live microorganisms that when given in adequate amounts, can provide health benefits to the host. 10 Probiotics usually promote health by regulating the endostasis of intestinal microorganisms, and Lactobacillus, Bifidobacterium and various probiotic complexes are widely used in UC alleviation studies.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, previous studies have shown that additional intake of beneficial bacteria can compete with harmful bacteria for adhesion sites and restore the balance of the intestinal flora, which is a target for treating UC. 9…”
Section: Introductionmentioning
confidence: 99%
“…Alterations and disruptions to the intestinal barrier are observed in patients with UC [ 77 ]. Several studies have reported gut microbiota and its metabolites altered intestinal permeability and promoted the level of intestinal tight junction proteins, such as claudin, and zonula occludens 1 (ZO-1) [ 78 80 ]. It has been reported that TCM could protect intestinal barrier via microbiota.…”
Section: Mechanisms Of Tcm Alleviating Uc Via the Gut Microbiotamentioning
confidence: 99%
“…Approaches aiming to reverse gut microbial disorders include dietary intervention, fecal microbiota transplantation (FMT), probiotic or prebiotic supplementation, etc. 30 Microbial nutriology has shown that the composition of gut microbiota is largely related to the host diet and the dietary structure. A long-term adherence of changing dietary habits and patterns can cause alteration in gut microbiota of the host.…”
Section: Significance Of Intestinal Flora and Remedy Thereofmentioning
confidence: 99%